2019
DOI: 10.3934/publichealth.2019.3.334
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of abdominal obesity and its correlates among adults in a peri-urban population of West Africa

Abstract: IntroductionPrevalence of abdominal obesity dramatically increases both in developed countries and in developing countries. In several regions in Africa, obesity (especially abdominal) is seen as a sign of affluence, dignity and respect. The objective of this study was to determine prevalence of abdominal obesity and seek some factors associated in a peri-urban population of West Africa.MethodsDuring April-May 2014, a cross-sectional study was conducted in Anonkoi 3, a neighborhood of Abidjan (Ivory Coast). Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
2
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 41 publications
8
22
2
8
Order By: Relevance
“…Similarly, women had higher measures of abdominal obesity compared to men. Our findings confirm what has been reported in other studies [ 17 , 19 – 21 ]. Likely reasons for this observation include that women are physiologically more predisposed to overweight and obesity due to the changes occurring during the reproductive years, and women have been reported to engage in less physically strenuous/demanding activities in the moderate to vigorous range compared to men in the same setting [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Similarly, women had higher measures of abdominal obesity compared to men. Our findings confirm what has been reported in other studies [ 17 , 19 – 21 ]. Likely reasons for this observation include that women are physiologically more predisposed to overweight and obesity due to the changes occurring during the reproductive years, and women have been reported to engage in less physically strenuous/demanding activities in the moderate to vigorous range compared to men in the same setting [ 21 ].…”
Section: Discussionsupporting
confidence: 94%
“…However, the prevalence of abdominal obesity was much higher in studies conducted in various countries [ 16 20 ] as compared to this study. Similar to the previous studies [ 13 17 , 19 , 20 ], this study also found a higher prevalence of abdominal obesity in females (27.3%) than in males (20.6%).…”
Section: Discussionsupporting
confidence: 91%
“…Prevalensi obesitas di wilayah perkotaan teridentifikasi lebih tinggi (K. Malik et al, 2019). Prevalensi paling rendah teridentifikasi pada kelompok pria di wilayah perkotaan Brazil, sebesar 11,9% (Bezerra & Sichieri, 2009).…”
Section: Diskusiunclassified
“…Faktor internal selanjutnya adalah jenis kelamin. Prevalensi obesitas lebih banyak ditemukan pada perempuan dibandingkan laki-laki (K. Malik et al, 2019;Khusun et al, 2015;Saquib et al, 2016;Somasundaram et al, 2019). Seluruh penelitian yang mengaitkan jenis kelamin dengan obesitas menunjukkan hal yang sama.…”
Section: Faktor Internal a Faktor Internal Yang Tidak Dapat Diubahunclassified
“…In Xinjiang Province in China the prevalence of obesity and overweight are 26.5% and 36.5% respectively with female dominance [6]. In Cote D'Ivoire 50.8% of adults have abdominal obesity [7] while the most recent South African Demographic Health Survey (SADHS 2016) estimated the prevalence of overweight/obesity among South Africans to be 68% and 31% for women and men respectively [8]. A study conducted by Lartey et al (2019) observed increasing prevalence of overweight/ obesity among Ghanaians [9].…”
Section: Introductionmentioning
confidence: 99%